The Role of Radio Nepal in Constructing Newar Linguistic and Cultural Identity - Maharjan, Upesh (Mangal Research Journal, 2025)
This study examines the role of Radio Nepal's Nepal Bhasa program in building linguistic, cultural, and musical identity. It also explores how the program influences, helps create or maintain identities, and preserves existing forms in Nepal’s diverse multilingual media ecosystem. A triangulated mixed-methods design was used, consisting of a survey of 18 regular listeners, 10 key informant interviews, 10 Jeewan Daboo interviews, and content analysis of 70 Nepal Bhasa news bulletins. Survey data shows that 68% of respondents regularly listen to the broadcasts, while 82% state they personally benefit from a better understanding of language, culture, and identity. The qualitative findings suggest a strengthening of linguistic authenticity through the use of native vocabulary and idiomatic expression, along with cultural continuity based on storytelling, music, festivals, and the Nepal Bhasa Movement. This content analysis acknowledges that indigenous vocabulary is commonly used. Listeners wanted more airtime, prime-time scheduling, and expert-led content. Overall, the research highlights how Radio Nepal offers a vital space for maintaining Newar identity and the implications of inclusive media policy for minority languages.